Recursos directamente recaudados y su incidencia en la ejecución presupuestal de la Región Loreto periodo 2017 – 2021 - Valiente Ferreira, Christian Jaker (2025)
The analysis of the resources directly collected and the budget execution of the Regional Government of Loreto between 2017 and 2021 reveals a significant relationship between income and expenses. The results show a strong positive correlation (0.9210) between both, indicating that an increase in income is associated with a proportional increase in expenses. The linear regression model suggests that approximately 85% of the variability in expenses can be explained by income, validating its use for financial forecasting. However, the Shapiro-Wilk test indicates possible non-normality in the "spending" data, which could affect the accuracy of the model. The insignificance of the constant suggests the need to include other factors in the analysis to better capture spending dynamics. Overall, these results highlight the importance of optimizing financial management and diversifying revenue sources to ensure efficient utilization of public resources in Loreto.